Preseason and post season body composition does not change relative to playing time in Division I female basketball players - Ladwig, E.; Shim, A. L.; Yom, J. P.; Cross, P.; Beebe, J. (International Journal of Exercise Science, 2013)
The purpose of the study was to determine if preseason and postseason body fat percentages (BF%) change relative to playing time in Division I women`s basketball players. Subjects for the study included 11 National Collegiate Athletic Association (NCAA) Division I female collegiate basketball athletes over the age of 18 from a Midwest public university. Demographic data of each subject (age 20.09 +1.81 yrs., weight 71.13 +10.85 kg., height 176.48 + 8.33 cm.) was taken before the initial body fat assessment. The subjects underwent preseason and postseason BOD POD® testing to get an accurate measure of body fat percentages. Data analyses looked for changes between preseason and postseason body fat percentage. A Pearson`s Correlation was performed to determine if changes in preseason and postseason BF% changed relative to playing time. Body fat percentage varied across preseason and postseason (average decrease in BF%: -1.83%) but such a difference was not significant (t1,10 = 1.89, p = .088). A negative relationship was found between preseason BF% and playing time (r = -.707) and postseason BF% and playing time (r =-.728). No relationship was found between change in BF% and playing time.